Bcl2-induced DNA replication stress promotes lung carcinogenesis in response to space radiation. (11th March 2020) - Xie, Maohua; Park, Dongkyoo; Sica, Gabriel L; Deng, Xingming
Abstract: Space radiation is characterized by high-linear energy transfer (LET) ionizing radiation. The relationships between the early biological effects of space radiation and the probability of cancer in humans are poorly understood. Bcl2 not only functions as a potent antiapoptotic molecule but also as an oncogenic protein that induces DNA replication stress. To test the role and mechanism of Bcl2 in high-LET space radiation-induced lung carcinogenesis, we created lung-targeting Bcl2 transgenic C57BL/6 mice using the CC10 promoter to drive Bcl2 expression selectively in lung tissues. Intriguingly, lung-targeting transgenic Bcl2 inhibits ribonucleotide reductase activity, reduces dNTP pool size and retards DNA replication fork progression in mouse bronchial epithelial cells. After exposure of mice to space radiation derived from 56 iron, 28 silicon or protons, the incidence of lung cancer was significantly higher in lung-targeting Bcl2 transgenic mice than in wild-type mice, indicating that Bcl2-induced DNA replication stress promotes lung carcinogenesis in response to space radiation. The findings provide some evidence for the relative effectiveness of space radiation and Bcl-2 at inducing lung cancer in mice. Abstract : Here we have discovered that Bcl2 potently promotes lung cancer development in response to space radiation. Our findings contribute to the development of new strategies for the prevention and/or treatment of space radiation-induced lung cancer by disrupting the oncogenic activity of Bcl2.